Experimental studies of the kinetics of infrared drying of spent coffee grounds - Burdo, Oleg; Bezbakh, Igor; Shyshov, Serhii; Zykov, Aleksandr; Gavrilov, Aleksander; Vsevolodov, Oleksandr; Sirotyuk, Ilya; Terziev, Sergey (Technology audit and production reserves, 2019)
The object of research is drying of spent coffee grounds. In modern production, the issues of rational use of energy in all processes of food technology, including drying, are urgently raised. In many food technologies, 2–3 times more energy is used than is physically necessary for the process. This determines the energy intensity of production and the quality of products. Drying processes are among the most energy-intensive, and in many cases the proportion of energy in the cost of production is up to 30 %. When drying of spent coffee grounds, convective dryers are mainly used, the energy consumption of which is 5 MJ/kg of removed moisture and above. Convective drying uses 40 % of the supplied energy to evaporate moisture. Also, a significant drawback of convective dryers is the discharge of waste coolant into the atmosphere, which has a heat content of only 10–15 % less than the hot air supplied to the drying chamber. The paper proposes the use of infrared radiation for drying of spent coffee grounds in periodic and continuous units. This will allow in the future to reduce specific energy consumption. During the study, the influence of the energy supply intensity, temperature, air flow rate, product layer thickness and specific load on the kinetics of periodic infrared drying of spent coffee grounds is determined. The influence of the energy supply intensity, specific load, tape speed, and the number of infrared modules on the kinetics of continuous infrared drying of spent coffee grounds is determined. The results are compared with convective drying in terms of specific energy consumption. A feature of the use of infrared radiation is its high efficiency and high rate of moisture removal from the surface layers of spent coffee grounds, and as a result, an increase in the productivity of the drying method and a decrease in specific energy consumption. The specific energy consumption obtained during operation of infrared drying of spent coffee grounds is 3.2 MJ/kg. This is below existing convection dryers.